LEGAL REVIEW OF FREEDOM OF CONTRACT IN VENTURE CAPITAL INVESTMENT AGREEMENTS - Nadhila Desya; Rachmad Abduh (Inspiring Law Journal, 2026)
An agreement is a legal relationship between two or more parties who agree to carry out an action. An agreement begins with a statement of commitment from the parties. One of the principles that must be respected when drafting an agreement is freedom of contract, which means giving the parties the opportunity to reach an agreement. However, freedom of contract raises legal challenges, especially because it protects the interests of the parties. Therefore, legal review of freedom of contract in venture capital investment agreements has an important role in ensuring that freedom of contract and adequate legal protection are balanced to avoid disputes that may arise.The type of research used is normative, employing qualitative analysis techniques, which are then described and analyzed using descriptive methods. The approach used in this study is a statutory approach, namely by understanding and reviewing regulations related to this research.The results of the research and discussion in this study are that the principle of freedom of contract in venture capital investment agreements is implemented through the freedom of the parties in determining the form of the agreement content, capital participation, profit sharing and the mechanism for terminating the agreement. Legal protection for the parties is also realized through the principle of good faith and the principle of balance from the formation stage of the agreement to its termination. Freedom of contract in venture capital investment agreements is also limited by applicable legal provisions including, among others, the requirements for the validity of the agreement as regulated by the Civil Code and special regulations in the field of venture capital.